2015
DOI: 10.1016/j.celrep.2015.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Transcriptional Signature in Neutrophils and Low-Density Granulocytes Are Associated with Tissue Damage in Malaria

Abstract: SUMMARY Neutrophils are the most abundant leukocyte population in the bloodstream, the primary compartment of Plasmodium sp. infection. Yet, the role of these polymorphonuclear cells in mediating either resistance or pathogenesis of malaria is poorly understood. We report that circulating neutrophils from malaria patients are highly activated, as indicated by a strong type I interferon transcriptional signature, increased expression of surface activation markers, the enhanced release of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 50 publications
8
114
2
1
Order By: Relevance
“…Many different cell types produce Type I IFNs. Transcription of Type I IFNs has been shown for pDCs and to a lesser extent cDCs3536, and neutrophils have an Interferon transcriptional signature during P. vivax infection37. Most of these cells are not located within the brain; however with disruption of the BBB it is possible that cytokines such as IFNs access the brain parenchyma and thus microglia by this route.…”
Section: Resultsmentioning
confidence: 99%
“…Many different cell types produce Type I IFNs. Transcription of Type I IFNs has been shown for pDCs and to a lesser extent cDCs3536, and neutrophils have an Interferon transcriptional signature during P. vivax infection37. Most of these cells are not located within the brain; however with disruption of the BBB it is possible that cytokines such as IFNs access the brain parenchyma and thus microglia by this route.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, IFN-I-signalling was reported to induce Bcl6, CXCR5 and PD1 expression in naïve CD4 + T cells following TCR stimulation in vitro [37]. IFN-I-related immune responses have also been observed in PBMC from malaria patients [38,39,40]. Although their functional relevance in humans remains to be established, we recently showed in ex vivo cultures of PBMC from P .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis carried out in mice with blood-stage infection with P. berghei revealed that IFN regulatory factors were upregulated during the acute phase (41). Induction of a typical type I IFN signature was also observed in hepatocytes from mice infected with P. berghei and P. chabaudi sporozoites, where genes such as Mda, Irf3, Irf7 , and Stat1 were upregulated (4244). Similar results were observed in humans.…”
Section: Protozoan Parasites and Ifn-imentioning
confidence: 90%
“…Similar results were observed in humans. Patients infected with P. vivax and P. falciparum showed a predominantly IFN-I transcriptional signature during the mild and the severe phase of infection (44, 45). …”
Section: Protozoan Parasites and Ifn-imentioning
confidence: 99%